Superior performance of African runners in warm humid but not in cool environmental conditions - Marino, F. E.; Lambert, M. I.; Noakes, T. D. (Journal of Applied Physiology, 2003)
The purpose of this study was to examine the running performances and associated thermoregulatory responses of African and Caucasian runners in cool and warm conditions. On two separate occasions, 12 (n = 6 African, n = 6 Caucasian) well-trained men ran on a motorized treadmill at 70% of peak treadmill running velocity for 30 min followed by an 8-km self-paced performance run (PR) in cool (15°C) or warm (35°C) humid (60% relative humidity) conditions. Time to complete the PR in the cool condition was not different between groups (27 min) but was significantly longer in warm conditions for Caucasian (33.0 ± 1.6 min) vs. African (29.7 ± 2.3 min, P < 0.01) runners. Rectal temperatures were not different between groups but were higher during warm compared with cool conditions. During the 8-km PR, sweat rates for Africans (25.3 ± 2.3 ml/min) were lower compared with Caucasians (32.2 ± 4.1 ml/min; P < 0.01). Relative rates of heat production were less for Africans than Caucasians in the heat. The finding that African runners ran faster only in the heat despite similar thermoregulatory responses as Caucasian runners suggests that the larger Caucasians reduce their running speed to ensure an optimal rate of heat storage without developing dangerous hyperthermia. According to this model, the superior running performance in the heat of these African runners can be partly attributed to their smaller size and hence their capacity to run faster in the heat while storing heat at the same rate as heavier Caucasian runners.